2018
DOI: 10.1111/epi.14032
|View full text |Cite
|
Sign up to set email alerts
|

White matter spongiosis with vigabatrin therapy for infantile spasms

Abstract: The histopathology, "white matter spongiosis," defined by electron microscopy (EM) as "intramyelinic edema," has been associated with vigabatrin therapy in various animal models, but its role or significance in clinical studies is unknown. We conducted a neuropathological examination on a 27-month-old boy with bilateral polymicrogyria and epilepsy after sudden unexpected death in epilepsy (SUDEP). The patient was initiated on vigabatrin at 4 months of age, which controlled infantile spasms, and was continued a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Findings were felt to be consistent with VGB toxicity. [14][15][16] Case 2 was a 20-month-old female with hemimegalencephaly and perisylvian polymicrogyria with a variant of unknown significance in the MTOR gene. She developed IS at 3 months but was lost to follow-up until 6 months of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings were felt to be consistent with VGB toxicity. [14][15][16] Case 2 was a 20-month-old female with hemimegalencephaly and perisylvian polymicrogyria with a variant of unknown significance in the MTOR gene. She developed IS at 3 months but was lost to follow-up until 6 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…19 In human infants receiving VGB, VABAM is associated with higher peak and average doses. 12 Pearl et al 15 recently described a case of sudden unexpected death in epilepsy in a 27-month-old with complex cerebral malformations on VGB for 13 months. On autopsy, spongiform white matter vacuolation was noted in the brainstem, including the medullary reticular formation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which VGB selectively affects the visual system has not been clearly defined (Shields and Pellock 2011;Tugcu et al 2017;Peng et al 2017;Yang et al 2012), while other studies suggest that VGB does not display an increased association with visual field abnormalities (Schwarz et al 2016). More recently, VGB has been associated with white matter spongiosis and restricted globus pallidus diffusion (Pearl et al 2018;Trindade et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…25,33 It has been suggested that VGB-induced elevation of ocular/retinal GABA induces excitotoxicity via GABAergic receptors, [34][35][36] resulting in oxidative stress. [37][38][39][40] Other studies have suggested globus pallidi and white matter anomalies associated with chronic VGB intake, [41][42][43] and pathological roles for amino acids (ornithine, taurine) that share structural and biochemical properties of GABA have also been implicated in VGB-associated ocular toxicity. 29,44,45 Thus, there is no clear consensus as to the mechanism(s) of potential VGB ocular toxicity.…”
Section: Discussionmentioning
confidence: 99%